Gaps between policy, protocols and practice: a qualitative study of the views and practice of emergency ambulance staff concerning the care of patients with non-urgent needs. Issue 4 (1st August 2005) - Snooks, H A; Kearsley, N; Dale, J; Halter, M; Redhead, J; Foster, J
Abstract : Aim: To describe emergency ambulance crews' views about (1) how they make decisions on whether to convey patients to hospital; (2) an intervention enabling them to triage patients to non-conveyance; and (3) their experience of using new protocols for undertaking such triage. Methods: Two focus groups were held at the outset of an evaluation of Treat and Refer (T&R) protocols: one with staff based at an ambulance station who were to implement the new service (intervention station), and the other with staff from a neighbouring station who would be continuing their normal practice during the study (control station). A third session was held with staff from the intervention station following training and 3 months' experience of protocol usage. Results: Before the introduction of the T&R protocols, crews reported experience, intuition, training, time of call during shift, patient preference, and home situation as influencing their decisions concerning conveyance. Crews were positive about changing practice but foresaw difficulties with advising patients who wanted to go to hospital, and with referral to other agencies. Following experience of T&R protocol use, crews felt they had needed more training than had been provided. Some felt their practice and job satisfaction had improved. Problems with referral and with persuading some patients that they did not need to go to hospital were discussed. There was consensus that the initiative should be introduced across the service. Conclusions: With crews generally positive about this intervention, an opportunity to tackle this difficult area of emergency care now exists. This study has, however, highlighted the complexity of the change in practice and service delivery, and professional and organisational constraints that need to be considered.